Data of feather recovering performance of birds and micro structure of pigeons’ feathers - Jing-Shan Zhao; Jiayue Zhang; Yuping Zhao; Zhaodong Zhang; Pascal Godefroit (Data in Brief, 2020)
Data is presented to explain why birds can recover their ruffled feather vanes by shaking wings and preening feathers with the beak [1]. Presented data includes the SEM microscopic images of rachis, barbs and barbules of pigeon's feather and the images recording the experiments of observing and mimicking the recovering performance of pigeons. Besides, based on the measurement and observation of the micro structure of feathers, the mechanical models of barbules were developed to better understand the wings performance. These high-quality images and models could be used for future research on feathers. Data helps to better understand the micro structure of feathers and the reason birds can fly. Data also support bioinspired mechanical structure development, especially for flapping robot development. Keywords: Feather, Hierarchical vane structure, Self-healing, Flapping robot